PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION BERBASIS PENILAIAN KINERJA TERHADAP KOMPETENSI PENGETAHUAN MATEMATIKA SISWA KELAS V SD GUGUS II KUTA UTARA TAHUN PELAJARAN 2017/2018 - Ni Luh Nita Suci Widiasih (Journal for Lesson and Learning Studies, 2018)
This research aimed to determine the influence of learning model team assisted individualization, based dreaded performance against the competency knowledge mathematic students of class V elementary school Gugus II Kuta Utara in the academic year 2017/2018. This research is an experimental research with the research design is quasi-exsperimental design ( nonequivalent control group design). The population in this research is all class V elementary school Gugus II Kuta Utara in the academic years 2017/2018 as many as 334 students. Research sample is determined by random sampling technique. The sample in this research is class V elementary school No. 3 Canggu as experimental group and class VB elementary school No. 1 Tibubeneng as control group. That amounts 66 students. The mathematic knowledge competence control data is collected with instruments in the from of multiple choice test. Than the data is analyzed by t-test. The result of the analysis shows that there is a significant difference of mathematic knowledge competence among group of students who are tought using learning model team assisted individualization based dreaded performance and teach using konvensional learning on the students class V elementary school Gugus II Kuta Utara academic year 2017/2018. This is evidenced by the Tcount of = 4,072 > Ttable = 2,000 at the significant level of 5% with DK = n1+n2-2 (33+33-2=64). Similary the average score of knowledge competence of mathematic student experimental group = 75,71 >  = 61,00 average of mathematic knowledge competence of control group students. This it can concoulde that the application of model team assisted individualization based dreaded performance against of competency mathematic knowledge students class V elementary school Gugus II Kuta Utara academic yesrs 2017/2018.